"Time-Based Paintings": Jeremy Blakes Winchester Trilogy (2001-2004) - Teine, Sonja (Current Objectives of Postgraduate American Studies, 2012)
Sarah Winchester, heiress of the rifle fortune, felt that she was cursed by the spirits of the ones who had been killed by the Winchester rifles. She sought out spiritualists who told her to move west and build a house: The sounds of construction should ward off the ghosts. Thus in 1884 she moved to San Jose, purchased a farm house and immediately began spending her 20 million inheritance on renovating the house, with work continuing 24 hours a day, 7 days a week, 365 days a year for the next 38 years. Construction only stopped on the Winchester Mystery House upon her death in 1922, when the workers immediately stopped building. It is now a Disney-like tourist attraction with guided tours through the oddities of the 160-chamber-mansion built in victorian style.Jeremy Blake, a young american artist living in Los Angeles, was fascinated by this story and used it as the basis of one of his latest art works called The Winchester Trilogy“. The essay shows how Blake created a multimedia video-sound-installation, which equally enthralls and repells its audience with amazing colors and disturbing pictures. Blake dispensed with plot, instead he put emphasis on our visual memory, which is influenced by the many cowboy-, horror- and wild west Hollywood-movies. Thus the Winchester Trilogy“ not only is an amazing piece of contemporary art but it is also a statement about the american myth of freedom, which has to be protected by the power of weapons.